Influence of female sex and fertile age on neuromyelitis optica spectrum disorders - Borisow, Nadja; Wildemann, Brigitte; Jarius, Sven (Multiple sclerosis journal, 2016)
Background: Gender and age at onset are important epidemiological factors influencing prevalence, clinical presentation, and treatment response in autoimmune diseases.Objective:To evaluate the impact of female sex and fertile age on aquaporin-4-antibody (AQP4-ab) status, attack localization, and response to attack treatment in patients with neuromyelitis optica (NMO) and its spectrum disorders (neuromyelitis optica spectrum disorder (NMOSD)).Methods:Female-to-male ratios, diagnosis at last visit (NMO vs NMOSD), attack localization, attack treatment, and outcome were compared according to sex and age at disease or attack onset.Results:A total of 186 NMO/SD patients (82% female) were included. In AQP4-ab-positive patients, female predominance was most pronounced during fertile age (female-to-male ratio 23:1). Female patients were more likely to be positive for AQP4-abs (92% vs 55%; p?40?years.Conclusion:Our data suggest an influence of sex and age on susceptibility to AQP4-ab-positive NMO/SD. Genetic and hormonal factors might contribute to pathophysiology of NMO/SD.